On Projective Modules and Computation of Dimension of a Module over Laurent Polynomial Ring. (12th June 2011) - Mishra, Ratnesh Kumar; Kumar, Shiv Datt; Behara, Srinivas
Abstract : We give a procedure and describe an algorithm to compute the dimension of a module over Laurent polynomial ring. We prove the cancellation theorems for projective modules and also prove the qualitative version of Laurent polynomial analogue of Horrocks' Theorem.